Sociodemogra phic, clinical, and laboratory profiles of patients with early- versus late-onset systemic lupus erythematosus. A single-center observational study in the Colombian Caribbean (2025)
Introduction: Late-onset systemic lupus erythematosus (SLE) is a rare form of this disease characterized by atypical clinical manifestations and a high burden of comorbidities, making it challenging to diagnose and manage patients in time. The objective of this study was to compare the sociodemographic, clinical, and paraclinical characteristics, as well as the therapeutic outcomes, of patients with earlyand late-onset SLE in a reference center in the Colombian Caribbean. Methods: This was an observational, descriptive, and cross-sectional study based on a review of medical records from the RENELUP database (2010–2024). Patients aged ≥18 years who met the 2019 EULAR/ACR criteria were included. Chisquare, Fisher's, and Student's T tests were applied. Results: A total of 282 patients were analyzed: 235 (83%) with early-stage SLE and 47 (17%) with late-stage SLE. Females predominated (89% and 81%, respectively). Patients with late-stage SLE had higher proteinuria (2,900 vs. 662 mg/24 h; P<0.001) and lower HDL levels (41 vs. 48 mg/dl; P=0.038). There were no significant differences in remission or mortality, although mortality was higher for late-stage disease (20.7% vs. 10.1%). Conclusion: Patients with late SLE had a lower frequency of typical clinical manifestations, including mucocutaneous, joint, and hematological involvement. In terms of renal involvement, patients with late SLE had a higher burden of proteinuria, with no statistically significant differences in mortality or remission rate.